Jury instructions and mock-juror sensitivity to confession evidence in a simulated criminal case - O’Donnell, Christina M. (Psychology, crime & law, 2017)
We investigated whether enhanced jury instructions, which added empirical findings about confession evidence to standard jury instructions, could sensitize mock jurors to the confession evidence in a criminal trial transcript. Participants (N = 314) read a detailed transcript of a simulated murder trial, followed by standard or enhanced jury instructions. The key evidence was the defendant’s recanted confession, gathered by police using either coercive (weak case) or appropriate (strong case) tactics. For example, testimony in the weak case, but not the strong case, indicated that the suspect was likely intoxicated when interviewed, and that the police likely lied about the evidence against him and hinted at leniency if he confessed. Participants in the enhanced instruction groups rated the likelihood that the defendant killed the victim as significantly higher in the strong case than the weak case, and they were also significantly more likely to find the defendant guilty in the strong case. In contrast, participants in the standard instruction groups did not differ significantly in either rated likelihood of killing or verdict for the two cases. The results demonstrate that instructions can make jurors sensitive to the strength of confession evidence, rather than merely skeptical about confession evidence.